Histoenzymic Localization of Oxidoreductases and Phosphatases in the Tonsils of Naso-pharyngeal region of Buffaloes - Pawan Kumar,; Amandeep Singh,; Tej Parkash,; Parveen Kumar Gahlot, (Indian Journal of Veterinary Anatomy, 2026)
The present study was aimed to explore the localization of oxidoreductases and phosphatases enzymes in the nasopharyngeal, tubal and paraepiglottic tonsils of six adult healthy buffaloes. The succinic dehydrogenase,  lactic dehydrogenase, glucose-6-phosphate dehydrogenase and glutamic dehydrogenase showed a strong positive activity in the pseudostratified columnar ciliated epithelium and stratum basale layer of the stratified squamousepithelium of the tonsils. The diffuse lymphoid tissue and the striated muscles showed moderate to strongpositive reactions. The mucous secretory acini did not show any affinity for these enzymes, however, a uniformmoderate to strong positive reaction was observed towards their basement membranes. The acid and glucose-6-phosphatases showed a moderate activity in the respiratory epithelium and the deepest layer of cells next tothe basement membrane of the stratified squamous epithelium. The associated submucosal lymphoid tissueand the glandular tissue of the tonsils showed positive reactions like those of the oxidoreductases group of enzymes. A comparison of the pattern of localization of these enzymes in healthy and infected animals mayplay a significant role in disease diagnosis, if any.